VaERD15, a Transcription Factor Gene Associated with Cold-Tolerance in Chinese Wild Vitis amurensis - Yu, Dongdong; Zhang, Lihua; Zhao, Kai; Niu, Ruxuan; Zhai, Huan; Zhang, Jianxia (Frontiers in Plant Science, 2017)
Abstract: Early responsive to dehydration (ERD) genes can be induced rapidly to counter some abiotic stresses, such as drought, low temperatures or high salinities. Here, we report an ERD gene (VaERD15) related to cold-tolerance from Chinese wild Vitis amurensis accession ‘Heilongjiang seedling’. The full-length of VaERD15 cDNA is 685 bp including 66 bp 5′-untranslated region (UTR), 196 bp 3′ -UTR region and a 423 bp ORF (open reading frame) encoding 140 amino acids. The VaERD15 protein shares a high amino acid sequence similarity with ERD15 of Arabidopsis thaliana. In our study, VaERD15 proved to have a nucleic localization function and a transcriptional activation function. Semi-quantitative PCR and Western blot analyses showed that VaERD15 was constitutively expressed in young leaves, stems and roots of V. amurensis accession ‘Heilongjiang seedling’ plants but the expression levels increased after low-temperature treatment. We also generated the over-expression transgenic line of VaERD15 in Arabidopsis Col-0 and carried out a cold treatment assay. The qRT-PCR and western blot analyses showed that with the increasing duration of cold treatment, the expression both in gene and protein levels was raised continuously in transgenic plants, and almost nothing was detected in the wild type arabidopsis. Moreover, the VaERD15 over-expression plants showed higher cold tolerance and the accumulations of proline, soluble sugars and proteins, malondialdehyde and three antioxidases (superoxide dismutase, peroxidase and catalase). Lower levels of relative ion leakage also occurred under cold stress. Together, our results indicate that the transcription factor VaERD15 was induced by cold stress and that it also enhanced cold tolerance.